2017
DOI: 10.1007/jhep10(2017)094
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-mediated dark matter annihilation in the Randall-Sundrum model

Abstract: Observational evidence for dark matter stems from its gravitational interactions, and as of yet there has been no evidence for dark matter interacting via other means. We examine models where dark matter interactions are purely gravitational in a RandallSundrum background. In particular, the Kaluza-Klein tower of gravitons which result from the warped fifth dimension can provide viable annihilation channels into Standard Model final states, and we find that we can achieve values of the annihilation cross secti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 65 publications
1
45
0
Order By: Relevance
“…The cancellations are enforced by a set of sum rules [20] which inter-relate the masses and couplings of the various modes. 1112 In this paper we provide a detailed account of the calculations reported in [19,20], specifying all conventions 11 Spin-2 KK mode scattering was previously considered by [46], which used deconstruction to prove that the KK mode scattering amplitudes grew no faster than O(s 3 ) for a flat extra dimension. 12 Following the appearance of [19], and as [20] was being completed, the authors of [47] independently proved that the scattering amplitudes of helicity-zero modes of massive spin-2 KK modes in extra-dimensional theories grow only like O(s) for compactifications on arbitrary Ricci-flat manifolds.…”
Section: A Scattering Of Single Massive Spin-2 Particlementioning
confidence: 99%
See 1 more Smart Citation
“…The cancellations are enforced by a set of sum rules [20] which inter-relate the masses and couplings of the various modes. 1112 In this paper we provide a detailed account of the calculations reported in [19,20], specifying all conventions 11 Spin-2 KK mode scattering was previously considered by [46], which used deconstruction to prove that the KK mode scattering amplitudes grew no faster than O(s 3 ) for a flat extra dimension. 12 Following the appearance of [19], and as [20] was being completed, the authors of [47] independently proved that the scattering amplitudes of helicity-zero modes of massive spin-2 KK modes in extra-dimensional theories grow only like O(s) for compactifications on arbitrary Ricci-flat manifolds.…”
Section: A Scattering Of Single Massive Spin-2 Particlementioning
confidence: 99%
“…These extra-dimensional models are being probed by the LHC [8], where we can search for TeV scale KK excitations as a signature of physics beyond the Standard Model. Extra-dimensional theories that additionally incorporate neutral stable matter motivate certain dark matter models, where particulate dark matter interacts with the Standard Model through a massive spin-2 mediator (see, for example, [9][10][11][12][13][14][15]). 1 The extra-dimensional gravitational action in these models gives rise to interactions between the massive spin-2 KK resonances.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, for the particular choice of k and M 5 shown in Fig. 1, for a scalar DM particle the target freeze-out value σ FO v is achievable either through virtual radion/KK-dilaton exchange for low m DM or via real KK-graviton production for m DM a few TeV; for a fermion DM particle σ FO v is not achieved for m DM < 10 TeV; and, for a vector DM particle, the target relic abundance is achieved through virtual KK-graviton exchange for m DM ∼ 1 TeV (as it was found in the RS scenario [19,22]). On the other hand, a much larger value of m DM is needed to achieve the freeze-out target value if the DM particle is a fermion.…”
Section: Dm Annihilation Cross-section In Cw/ld Modelmentioning
confidence: 88%
“…In the Randall-Sundrum scenario it was known that, for scalar DM and SM particles localized in the IR brane, it is not possible to achieve σ FO v through the virtual KK-graviton or radion exchange channel (see also Refs. [19,22]). However, we showed that when the DM mass is large enough so that the direct production of KK-gravitons or radions becomes possible, then the correct relic abundance can be achieved for DM particle masses of a few TeV's, much as in the case of the CW/LD model studied here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation